Laju Reaksi Hidrolisis Herbisida Glifosat di Tanah Jenuh Air - Edia Rahayuningsih; Aswati Mindaryani; Mukti Mukti; Bostang Radjagukguk (Forum Teknik, 2006)
The objectives of the research were to find out the parameters of the hydrolysis reaction rate (k,,) and partition coefficien (Kr) of glyphosate herbicide in saturated soil system, to identify the variables affecting those parameters, and to develop the empirical equations corelating those parameters to the pertinent variables.The experimental work or physical simulation in laboratory was conducted in a batch reactor. The sterilized soil 5 gram put into a 1000 cm3 of Erlenmeyer glass and 500 cm3 of glyphosate solution with 8 g/1 concentration was added. The Erlenmeyer mouth was covered with plastic film and the entire Erlenmeyer surface was covered with aluminium foil to minimize vaporization and photolysis reaction. The solution was mixed continuously with magnetic stirrer. At the initial time and selected time intervals, 5 cm3 of the samples were taken with syringe. The samples were centrifuged and filtered, 1 cm3 of the filtrate were analyzed its glyphosate concentration with UV- VIS. The experiments were conducted for various soil types, and the empirical correlation between the hydrolysis reaction rate (k,,) and partition coefficien (Kr) with the affecting variables can be developed.Based on the laboratory data and the simulation of mathematical model, it could be concluded that the empirical correlation between the Kr and kh values with the affecting variables could be represented in the equations:Kr =11.035 (%organic matter) + 0.25 (%clay mineral) mL gramkh =1.0810 (%organic matter) + 1.5310-5 (%clay mineral) min-1